Seed germination ecology of junglerice (Echinochloa colona): a major weed of rice - Chauhan, Bhagirath S.; Johnson, David E. (Cambridge University Press, 2009)
Junglerice is one of the most serious grass weeds of rice in the tropics. Experiments were conducted in the laboratory and screenhouse to determine the influence of environmental factors on seed germination and seedling emergence of junglerice in the Philippines. In the laboratory, germination was stimulated by light, suggesting that seeds of this species are positively photoblastic. The tested temperatures (35/25, 30/20, and 25/15 C alternating day/night temperatures), however, did not influence germination. Germination in the laboratory was not affected by a soil pH range of 4 to 9, but was decreased by salinity (> 50 mM NaCl) and moisture stress (< −0.2 MPa osmotic potential). In the screenhouse, germination of junglerice was greatest (97%) for seeds at the soil surface, but emergence declined exponentially with increasing seed burial depth, and no seedlings emerged from seeds buried at 6 cm. In pots, seedling emergence declined markedly with the addition of rice residue to the soil surface at rates equivalent to 4 to 6 tonnes (t) ha−1. As germination of junglerice was strongly stimulated by light, and seedling emergence was optimal at shallow burial depths, this species is likely to be problematic in reduced tillage systems.